From drafts to drafting: genre work, time, and the fragility of managerial expertise in South Korea. Issue 6 (2nd November 2022) - Prentice, Michael M.
ABSTRACT: This article develops an approach towards managerial expertise as a practice organized around and dependent on what I describe as drafting time. The empirical focus is on an employee satisfaction survey at a South Korean conglomerate where I conducted ethnographic research between 2014 and 2015. Departing from approaches that see drafts in service of organizational function or as a production-line model, the article describes how drafting time is a state of work in which claims to expertise, and claims against a lack of expertise, are worked out away from the judgment of others. I describe how high-level human resources managers within the conglomerate Sangdo fashioned themselves as internal consultants through the development of a sophisticated employment survey. When the claims of the survey did not work out as they expected, they were able to re-draft their internal roles vis-a-vis other managers. The article highlights how drafting time is one way for knowledge workers to craft their expertise, particularly through the assemblage of different kinds of genres where their expertise might be properly recognized.